Study of the antimicrobial properties of certain saprophytic obligate marine fungi - Kalyuzhnaya, O (Annals of Mechnikov's Institute, 2020)
Today promising area of the development and introduction of new antimicrobial agents is to search for new antibiotics from natural sources, namely among marine organisms - microscopic fungi. Such saprophytic fungi as Ascomycota (families Arenariomyces, Ceriosporopsis, Corollospora, Halosphaeria) and Basidiomycota (family Nia), which are widely spreaded in Ukraine (salty estuaries and the coast of the Black Sea), are the objects of the study of this work. These types of marine organisms have been provided by the Odessa Branch of the Institute of Biology of the Southern Seas after collecting samples of water, sediment, cellulose substrates and subsequent isolation and obtain pure cultures by accumulation in the form fruiting bodies of Ascomycetes and Basidiomycetes - ascocarps and basidiocarps that can be stored 3-5 months in sterile seawater. The aim of this study was to investigate the presence of antimicrobial properties of saprophytic fungi obligate marine, which are characteristic for residents in Ukraine, namely the Black Sea. Materials and methods. At this stage the study of antimicrobial activity was performed by agar diffusion method and method of cocultivation of marine fungi with test strains in liquid culture medium. We have used reference strains of microorganisms: Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Bacillus subtilis ATCC 6633, Proteus vulgaris ATCC 6896, Pseudomonas aeruginosa ATCC 27853 and opportunistic fungus Candida albicans ATCC 885-653. Results and Discussion. Determination of antimicrobial activity by agar diffusion method showed that all samples had antimicrobial activity against the Gram-positive test strains (S. aureus and B. subtilis), effect for the Gram-negative bacteria (E. coli, P. vulgaris, P. aeruginosa) was much smaller or non-existent, and it isn’t observed against C. albicans (exclusion Nia vibrissa with zone of growth inhibition – 6.2 mm). The results of the counting of cells test strains of E. coli and S. aureus in control and after their cocultivation with fungi Halosphaeriopsis mediosetigera and Nia vibrissa on yeast broth at (37 ± 1) ° C showed that the number of test cells after culturing strains with selected species of marine fungi significantly lower than in control: when cultured with Halosphaeriopsis mediosetigera cell number of E. coli decreased by almost 100 times, and cells of S. aureus - 1000, when cultured with Nia vibrissa number of cells test strains decreased 100 times. These results prove the presence of antimicrobial properties for these species, with observed the same trend as the study of antimicrobial properties of agar diffusion method - both types of fungi inhibit gram-positive and gram-negative bacteria. Conclusions. The study of the antimicrobial properties of some species of saprophytic obligate marine fungi, which are the inhabitants of the north-western Black Sea region: Arenariomyces trifurcata, Ceriosporopsis halima, Corollospora maritima, Halosphaeriopsis mediosetigera, Nia vibrissa, was carried out. It was established that their culture supernatant have antimicrobial activity against gram-positive bacteria, and the last two species - against gram-negative bacteria, such action was not observed against C. albicans. Thus, the selected objects of study are potential producers of antimicrobial substances; it leads to the prospect of further work in this area.